APAKAH DIVERSITAS GENDER MEMENGARUHI STRUKTUR MODAL? BUKTI EMPIRIS DI INDONESIA - Suherman Suherman (Jurnal Keuangan dan Perbankan, 2017)
The purpose of this study is to know the influence of gender diversity that proxied by the existance and proportion of female directors in a firm on capital structure that proxied by debt to asset ratio (DAR) and debt to equity ratio (DER). Sample of this study consists of 78 firms (384 observations) listed on Kompas100 Index between 2011 and 2015. Controlling for firm size, profitability (ROA) and asset growth, the results show that 1)the existance of female on board of directors has positive and significant effect on DAR 2)female proportion on board of directors has no significant effect on DAR 3) the existance of female on board of directors has no significant effect on DER 4)female proportion on board of directors has no significant effect on DER